SMG1, a nonsense‐mediated mRNA decay (NMD) regulator, as a candidate therapeutic target in multiple myeloma. Issue 2 (16th December 2022) - Leeksma, Alexander C.; Derks, Ingrid A. M.; Garrick, Brett; Jongejan, Aldo; Colombo, Martino; Bloedjes, Timon; Trowe, Torsten; Leisten, Jim C.; Howarth, Michelle; Malek, Mehnaz; Mortensen, Deborah S.; Blease, Kate; et al.
Abstract : Early data suggested that CC‐115, a clinical molecule, already known to inhibit the mammalian target of rapamycin kinase (TORK) and DNA‐dependent protein kinase (DNA‐PK) may have additional targets beyond TORK and DNA‐PK. Therefore, we aimed to identify such target(s) and investigate a potential therapeutic applicability. Functional profiling of 141 cancer cell lines revealed inhibition of kinase suppressor of morphogenesis in genitalia 1 (SMG1), a key regulator of the RNA degradation mechanism nonsense‐mediated mRNA decay (NMD), as an additional target of CC‐115. CC‐115 treatment showed a dose‐dependent increase of SMG1‐mediated NMD transcripts. A subset of cell lines, including multiple myeloma (MM) cell lines sensitive to the endoplasmic reticulum stress‐inducing compound thapsigargin, were highly susceptible to SMG1 inhibition. CC‐115 caused the induction of UPR transcripts and cell death by mitochondrial apoptosis, requiring the presence of BAX / BAK and caspase activity. Superior antitumor activity of CC‐115 over TORK inhibitors in primary human MM cells and three xenograft mouse models appeared to be via inhibition of SMG1. Our data support further development of SMG1 inhibitors as possible therapeutics in MM. Abstract : In this study, SMG1, a key regulator of the RNA degradation mechanism nonsense‐mediated mRNA decay (NMD), was discovered as an additional target of the clinical compound CC‐115. CC‐115 treatment showed a dose‐dependent increase of NMD transcripts, unfolded protein response (UPR) transcripts, and cell death via SMG1 inhibition in a subset of cell lines, primary multiple myeloma cells, and xenograft mouse models.